If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(c + -3) + 4 = 3 + c + -11 Reorder the terms: 4(-3 + c) + 4 = 3 + c + -11 (-3 * 4 + c * 4) + 4 = 3 + c + -11 (-12 + 4c) + 4 = 3 + c + -11 Reorder the terms: -12 + 4 + 4c = 3 + c + -11 Combine like terms: -12 + 4 = -8 -8 + 4c = 3 + c + -11 Reorder the terms: -8 + 4c = 3 + -11 + c Combine like terms: 3 + -11 = -8 -8 + 4c = -8 + c Add '8' to each side of the equation. -8 + 8 + 4c = -8 + 8 + c Combine like terms: -8 + 8 = 0 0 + 4c = -8 + 8 + c 4c = -8 + 8 + c Combine like terms: -8 + 8 = 0 4c = 0 + c 4c = c Solving 4c = c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 4c + -1c = c + -1c Combine like terms: 4c + -1c = 3c 3c = c + -1c Combine like terms: c + -1c = 0 3c = 0 Divide each side by '3'. c = 0 Simplifying c = 0
| ln(0.5)/ln(X)=20 | | -n=5-6n^2+n | | 0.6x-2.6=0.4 | | 5(1+3b)=43+9b | | 8b^3-10b^3+3b=0 | | 2(4x+5)=-26+28 | | (-4-i)-(4+5i)=0 | | (6-2x)+4x=-x+1 | | -5v-6=9 | | 4d+(d-4)=45.75 | | 6/5y-9=-3 | | -5a+42=17 | | -49+2k=k-6k | | Log[8](3x+1)+16=18 | | 2/3x=-5/9 | | -13+a=60 | | -6(w-1)=-8w+14 | | 7z-10z=12 | | 2b^2+11=155 | | 6(x-4)=5x-1 | | -6v+6=-4(v-1) | | Ln*48-ln*x=ln*4w | | 20x*30=180 | | x^2+2x-100=180 | | h(t)=16t^2+40t+20 | | 2b^2+11=15 | | 294=12(n-3.50) | | -x-2=4x+3 | | 5-1/15x=1/10 | | 6p+1=13 | | 7x-3=28 | | x^2+2x+280=0 |